Time-Driven Activity-Based Costing in Practice: Physical Therapy Services - Taechoyotin, Wannee; Setthapronnan, Rinlita (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
This study demonstrates how to implement time-driven activity-based costing (TDABC) for physical therapy services. The main purpose of this study is to propose the unit cost calculation model that can be applied to other medical services. The unit cost from this study is from one-month operation and acts as an example and must be used with caution. Cost objects are physical therapy diagnoses while activities are treatments and time used in each treatment is indirect cost allocation bases. Using cost data from general ledgers ensures completeness of costs to be allocated. The average gross margin for the case in this study is 58%, ranging from 35% to 76% by diagnosis. Unit costs obtained from the analysis enable management to make informed future decisions regarding budget allocation and marketing campaigns to increase usage of underused capacity.